1997
DOI: 10.1073/pnas.94.22.11857
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory chain is required to maintain oxidized states of the DsbA-DsbB disulfide bond formation system in aerobically growing Escherichia coli  cells

Abstract: DsbA, the disulfide bond catalyst of Escherichia coli, is a periplasmic protein having a thioredoxin-like Cys-30-Xaa-Xaa-Cys-33 motif. The Cys-30-Cys-33 disulfide is donated to a pair of cysteines on the target proteins. Although DsbA, having high oxidizing potential, is prone to reduction, it is maintained essentially all oxidized in vivo. DsbB, an integral membrane protein having two pairs of essential cysteines, reoxidizes DsbA that has been reduced upon functioning. It is not known, however, what might pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
205
2
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 234 publications
(213 citation statements)
references
References 47 publications
5
205
2
1
Order By: Relevance
“…The major signal from the amino acid sequencing analysis was GKSMEN (corresponding to amino acids 73-78 of SpoIIQ), suggesting that extracellular cleavage occurs between Val-72 and Gly-73. Second, we constructed a series of SpoIIQ derivatives with individual cysteines introduced between codons 62 and 74 and used AMS modification (35) to determine if the cysteine residue was present in the C-terminal degradation product, which confirmed that in intact cells proteolysis occurred between Val-72 and Gly-73 (supplemental Fig. S1).…”
Section: Identification Of In Vivo Cleavagementioning
confidence: 95%
“…The major signal from the amino acid sequencing analysis was GKSMEN (corresponding to amino acids 73-78 of SpoIIQ), suggesting that extracellular cleavage occurs between Val-72 and Gly-73. Second, we constructed a series of SpoIIQ derivatives with individual cysteines introduced between codons 62 and 74 and used AMS modification (35) to determine if the cysteine residue was present in the C-terminal degradation product, which confirmed that in intact cells proteolysis occurred between Val-72 and Gly-73 (supplemental Fig. S1).…”
Section: Identification Of In Vivo Cleavagementioning
confidence: 95%
“…The redox states of proteins were assessed by modifying free thiol with AMS [11]. Briefly, after incubation with or without PDGF-BB, cell lysates or proteins were treated with trichloroacetic acid at a final concentration of 7.5% to denature and precipitate the proteins as well as to avoid any subsequent redox reactions.…”
Section: Determination Of Redox Statesmentioning
confidence: 99%
“…After overnight shaking, cells were diluted into the same medium for an additional 3 h of growth at 37°C. Cultures were directly treated with trichloroacetic acid (5%) to "freeze" the redox states of the proteins, which were dissolved in SDS solution containing AMS and subjected to SDS-PAGE and anti-DsbA immunoblotting (9). In this assay, reduced DsbA is mobility-shifted due to the AMS modification.…”
Section: Determination Of In Vivo Redoxmentioning
confidence: 99%
“…States of DsbA-E. coli strains CU141 (MC4100/FЈ, lacI q lacPL8 lacZ ϩ Y ϩ A ϩ pro ϩ ) (22), SS141 (CU141, dsbB::kan5) (3,23), TA36 (KS272, ubiA::Cm) (9), and AN384 (ubiA420 menA401) (21) were grown at 37°C in L-broth supplemented with 90 mM sodium phosphate (pH 7.5), 0.1 mM UQ1 (Sigma), and appropriate antibiotics. Exponentially growing cells were harvested by centrifugation, washed with the same medium without UQ1, and then re-inoculated into the UQ1-free medium.…”
Section: Determination Of In Vivo Redoxmentioning
confidence: 99%
See 1 more Smart Citation